(untitled) (Texas Journal of Engineering and Technology, 2023)
The lower limb is a marvel of anatomical engineering crucial for human mobility. This exploration emphasizes the foot’s intricate design and the ankle joint’s role in transmitting forces. Despite its remarkable design, the lower limb is prone to injuries, especially ankle injuries, disrupting daily life. Treatment options include ankle joint fixation, a surgical procedure employing pins, plates, rods, or screws. Gait analysis is vital for understanding walking patterns and intervention effectiveness. This study uses gait analysis methods to assess lower limb biomechanics. The research focuses on whole-body vibration’s impact on ankle joint stress, investigating leg stability, electromyography effects, ground reaction forces, and numerical analysis with ANSYS. Custom shoes tailored to patient needs based on studied parameters are explored . In the theoretical analysis, mechanical parameters affecting ankle joint stability, including the ankle moment and stress distribution, are examined. Mathematical analysis determines the center of mass and other parameters . Numerical analysis assesses stress, strain, deformation, and safety factors in the ankle joint. Stress patterns, strain distributions, deformation, and safety factors are discussed. The impact of different shoe designs on ankle mechanics, using the finite element method and ANSYS, is investigated. This research deepens our understanding of lower limb biomechanics and ankle joint health. By evaluating stress and vibration effects and designing custom shoes, it enhances ankle injury treatment and management strategies